Attention Deficits After Aneurysmal Subarachnoid Hemorrhage Measured Using the Test of Variables of Attention. Issue 5 (May 2015) - Wallmark, Svante; Lundström, Erik; Wikström, Johan; Ronne-Engström, Elisabeth
<x xml:space="preserve">Abstract</x> Background and Purpose— The aim of this pilot study was to assess attention deficits in patients with aneurysmal subarachnoid hemorrhage using the test of variables of attention (TOVA). This is a computer-based continuous performance test providing objective measures of attention. We also compared the TOVA results with the attention and concentration domains of Montgomery Åsberg Depression Rating Scale and Montreal cognitive assessment, 2 examiner-administrated neuropsychological instruments. Methods— Nineteen patients with moderate to good recovery (Glasgow outcome scale, 4–5) were assessed using the TOVA, Montgomery Åsberg Depression Rating Scale, and Montreal cognitive assessment. The measurements were done when the patients visited the hospital for a routine magnetic resonance imaging control of the aneurysm. Results— TOVA performance was pathological in 58%. The dominating pattern was a worsening of performance in the second half of the test, commonly a failing to react to correct stimuli. We found no correlation between TOVA and the performance in concentration and attention domains of Montgomery Åsberg Depression Rating Scale and Montreal cognitive assessment. Conclusions— Attention deficits, measured by the TOVA, were common after subarachnoid hemorrhage. This should be further studied to improve outcome.